Studi persepsi mahasiswa terhadap profesionalisme dosen akuntansi perguruan tinggi - Mas'ud Machfoedz (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 1999)
Sundem (1993) raised critics toward accounting education. His critics were followed by the concern of some academicians as well as practitioners. The concern mainly was about the level of the curriculum relevance's and more than that the professionalism of accounting educators. Here, in Indonesia there has also been similar problems. The degree of professionalism of accounting educators is still questionable.The purpose of this study is to answer the question: whether accountiung educators fulfill a certain degree of professionalism. The professionalism indicators of Novin and Tucker (1993) were used to research this concerning fact, namely: Knowledge, Skill, and characters.